GALLO, Ján: The expressing of the Category of Indeterminacy in Russian and Slovak. Nitra: Univerzita Konštantína Filozofa v Nitre 2008. 186 s - Pekaríková, Katarína (Jazykovedný časopis, 2010)
The article informs about new monograph that is focused on research of models of expressing of the category of indeterminacy comparing the Russian and Slovak languages. The author Ján Gallo leaves the traditional approach to the category of indeterminacy as grammatical category and, following works of S. A. Krylov, W. Gladrow, J. Kozílková and others, prefers semantic and functional approach and approach of pragmalinguistics. He explains this category from several points of view of the language system and points out, that perspectives of the following research could have a divergent character in linguistics.